LICHEN SPECIES DIVERSITY AS BIOINDICATOR OF AIR QUALITY IN THE GUNUNG BIBI FOREST, MOUNT MERAPI NATIONAL PARK - Irfan Agus Nugroho; Ananda Briliana Romadhona; Christabel Reviana Septianingtyas; Laila Nurul Ilma; Ari Satia Nugraha; Pairah Pairah; Ludmilla Fitri Untari; Andhika Puspito Nugroho (SEAMEO BIOTROP, 2025)
ARTICLE HIGLIGHTS- The study identified 36 lichen species from 14 different families.- The lichen composition differed between stations, indicating disparities in air quality.- Station II (1600-1700 masl) had better air quality than Station I (1600-1700 masl), which had a higher diversity index value and more lichen coverage. - Nitrogen emissions from farming may reduce the non-nitrophilic lichen diversity and abundance.- The diversity and abundance of lichen is affected by air temperature, humidity, light intensity, and the type of bark.ABSTRACTThe Mount Merapi ecosystem is distinguished by its considerable biodiversity potential, which has led to its designation as a national park and the protection of its unique ecological characteristics. A notable example of the Mount Merapi ecosystem is the Gunung Bibi forest, which has been designated as a Sanctuary Zone within the Mount Merapi National Park, with the primary objectives of biodiversity conservation, habitat preservation, and ecosystem protection. However, the Gunung Bibi forest is susceptible to the repercussions of volcanic eruptions and the pressure of agricultural activities from the surrounding area, which may potentially impact its air quality. Given the geographical area of the forest, the most efficient method for air quality monitoring is the use of lichens diversity as bio-indicators. This study aims to analyze the relationship between lichen species diversity and air quality in the Gunung Bibi forest area of Mount Merapi National Park, and the factors that influence it. Data collection was carried out by dividing the area into two research stations based on altitude. Data collection was carried out using a purposive sampling method with analysis including lichen abundance, lichen thallus cover area, and Shannon-Wiener Diversity Index measurement. Based on the research conducted, the results of lichen species diversity found at the research site include 36 species from 13 different families. The lichen composition at the two stations differs, indicative of disparities in air quality. Station II (1600-1700 masl) exhibited indications of better air quality in comparison to Station I (1500-1600 masl), which was distinguished by a higher diversity index value, as well as a greater lichen thallus covering area. The difference in air quality between the two research stations is probably due to nitrogen emissions from agricultural activities, which limit the diversity and abundance of non-nitrophilic lichen species Environmental factors affecting lichen species diversity and abundance are air temperature, humidity, light intensity, and bark type of lichen substrate.